A targeted resequencing gene panel for focal epilepsy. (26th April 2016) - Hildebrand, Michael S.; Myers, Candace T.; Carvill, Gemma L.; Regan, Brigid M.; Damiano, John A.; Mullen, Saul A.; Newton, Mark R.; Nair, Umesh; Gazina, Elena V.; Milligan, Carol J.; Reid, Christopher A.; Petrou, Steven; et al.
Abstract : Objectives: We report development of a targeted resequencing gene panel for focal epilepsy, the most prevalent phenotypic group of the epilepsies. Methods: The targeted resequencing gene panel was designed using molecular inversion probe (MIP) capture technology and sequenced using massively parallel Illumina sequencing. Results: We demonstrated proof of principle that mutations can be detected in 4 previously genotyped focal epilepsy cases. We searched for both germline and somatic mutations in 251 patients with unsolved sporadic or familial focal epilepsy and identified 11 novel or very rare missense variants in 5 different genes: CHRNA4, GRIN2B, KCNT1, PCDH19, and SCN1A . Of these, 2 were predicted to be pathogenic or likely pathogenic, explaining ∼0.8% of the cohort, and 8 were of uncertain significance based on available data. Conclusions: We have developed and validated a targeted resequencing panel for focal epilepsies, the most important clinical class of epilepsies, accounting for about 60% of all cases. Our application of MIP technology is an innovative approach that will be advantageous in the clinical setting because it is highly sensitive, efficient, and cost-effective for screening large patient cohorts. Our findings indicate that mutations in known genes likely explain only a small proportion of focal epilepsy cases. This is not surprising given the established clinical and genetic heterogeneity of these disorders and underscores the importance of further gene discovery studies in this complex syndrome.